2021
DOI: 10.1021/acs.macromol.1c01472
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Change of Poly(1-butene) during Crystallization, Phase Transition, and Melting Revealed by Synchrotron Small-Angle X-ray Scattering

Abstract: For a long time, polymer lamellar crystals were hard to characterize accurately and comprehensively. The main reason is that the small-angle X-ray scattering (SAXS) mechanism of semicrystalline polymers has not been elucidated thoroughly. In recent years, we examined SAXS in semicrystalline polymers carefully, finding that SAXS in semicrystalline polymers probably is from a new physical mechanism, that is, evanescent wave-induced scattering. Based on the finding, a full set of new characterization methodologie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…New development in data analysis can potentially introduce new findings with X‐ray data. Li et al 51 recently proposed new methodologies to interpret SAXS data from polymers crystallization based on evanescent wave‐induced scattering, so that the long period, lamellar thickness, and lateral size can be calculated more accurately. It was found that the lamellar size shrunk by 20% in lateral size and expand by 12% along the stem during phase transition of poly(1‐butene) form II to form I.…”
Section: Melt Memory Effects Of Semi‐crystalline Polymersmentioning
confidence: 99%
“…New development in data analysis can potentially introduce new findings with X‐ray data. Li et al 51 recently proposed new methodologies to interpret SAXS data from polymers crystallization based on evanescent wave‐induced scattering, so that the long period, lamellar thickness, and lateral size can be calculated more accurately. It was found that the lamellar size shrunk by 20% in lateral size and expand by 12% along the stem during phase transition of poly(1‐butene) form II to form I.…”
Section: Melt Memory Effects Of Semi‐crystalline Polymersmentioning
confidence: 99%
“…To observe the structural change from SAXS more clearly, SAXS was corrected with a new method proposed by us recently. [60][61][62][63] SAXS was first subtracted by free-melt scattering and then multiplied by q 4 . The aim of subtracting free-melt scattering is to remove other minor scatterings such as air scattering, scattering induced directly by incident X-ray.…”
Section: Nucleation Agent Morphologies Observed At Different Melting ...mentioning
confidence: 99%
“…7,8,13 Thus, to effectively regulate the mechanical properties, the study of the phase transition process is attracting more and more attention. 15–25 Over the past decades, various methods have been reported to tailor the phase transition process. 15,25–46 Qiao et al systematically investigated the correlation between temperature and phase transition kinetics.…”
Section: Introductionmentioning
confidence: 99%